Tasamuh Value As Conflict Resolution In Multickultural Society - Zebua, Ali M; Fauzi, Rahmat (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
Conflict in diversity is a problem that never stops. Even though the Indonesian state which has the philosophy of Unity in Diversity is seen as a country that upholds the value of tolerance, various diversity can live in harmony and peace in one area, but now the attitude of tolerance that this nation has is starting to fade and shift to intolerance by blaming each other, disbelieving each other. , and sometimes even lead to criminal acts. This conflict does not only occur between different religious communities, fellow religious people also often occur due to differences in views. The fading attitude of tolerance has become a serious conflict that can be fatal, so serious handling is needed on this matter. In fact, the government itself has always echoed the application of religious moderation, one of which is to make it happen by mutual respect and mutual respect. It is appropriate for the value of tasamuh to be reinterpreted to become a resolution of diversity conflicts. So the author describes the concept of tasamuh in this paper by analyzing verses related to tolerance. Through this paper, it can help in anticipating the occurrence of such diversity conflicts.